ANALISIS PERBANDINGAN KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN( STUDI KASUS PADA BENGKEL MOBIL ABADI MOTOR DAN BENGKEL MOBIL GUNTUR JAYA ABADI DI KOTA MATARAM) - MURJANA, I MADE; OKTAVIA, YUSI FAIZATHUL (GANEC SWARA, 2020)
This study aims to determine the level of customer satisfaction with the quality of service services at the Abadi Motor Car Workshop and the related Guntur Jaya Abadi Car Workshop (Tangible, Realibility, Responsiveness, Assurance and Emphathy),This research is comparative sampling with a sample size of 100. Nonprobability sampling technique is accidental sampling based on chance, who is doing car service is interviewed and given a questionnaire to fill out. The data analysis procedure used a Likert scale and t-test.Â The measurement results show that both workshops provide satisfactory service. However, the level of satisfaction at Bengkel Abadi Motor is higher than Guntur Jaya Abadi. This is shown by the comparison of the t-test, the mean value of the differences in the 5 dimensions of service quality has a value of t count = 10.899. in the t value distribution table, namely at the confidence level of 95% and Î± = 5% because the t test is two-sided, the referred Î± value is Î± / 2 (0.050 / 2 = 0.025) and (dk) = n-1 = 70- 1 = 69 so that t table = 2.009. It is said that there is a difference if the t value> t table. So with an average t value of = 10,889> 2,009 with a significance of 0,000, it can be said that there is a difference in service quality in the two workshops.